2018
DOI: 10.1016/j.heliyon.2018.e01103
|View full text |Cite
|
Sign up to set email alerts
|

Toughness, elasticity and physical properties for the evaluation of foamed concrete reinforced with hybrid fibers

Abstract: This study has been undertaken to investigate the evaluation of Fiber-reinforced Foamed Concrete (FRFC) performance by the use of toughness and non-destructive tests. These tests cover the workability, density, static modulus of elasticity, toughness, ultrasonic pulse velocity and absorption tests. Different FRFC mixes using carbon fibers in the order of 0.5, 1 and 1.5% carbon fibers were used. Also, the combinations of carbon fibers (C) and polypropylene fibers (PP) as 1% C+ 0.5% PP, and 0.5% C+1% PP were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The flow time should be within 20 s so that a sufficient amount of the mixture is placed in the mold and self-sealing without any external devices [ 8 , 55 ]. Reportedly, [ 159 , 160 ], various factors affect the mixture’s consistency and rheology; which are mainly associated with the components and technology of the mixture. For this, the mixture’s components must be precisely calculated to improve the rheology and consistency of FRFCC, attain self-sealing behaviors, and enhance the adhesion and cohesion between the foaming agent and the cementitious filler.…”
Section: Properties Of Frfcmentioning
confidence: 99%
“…The flow time should be within 20 s so that a sufficient amount of the mixture is placed in the mold and self-sealing without any external devices [ 8 , 55 ]. Reportedly, [ 159 , 160 ], various factors affect the mixture’s consistency and rheology; which are mainly associated with the components and technology of the mixture. For this, the mixture’s components must be precisely calculated to improve the rheology and consistency of FRFCC, attain self-sealing behaviors, and enhance the adhesion and cohesion between the foaming agent and the cementitious filler.…”
Section: Properties Of Frfcmentioning
confidence: 99%
“…Adopted hybridization ensures multi-scale resistance to cracking (Cattaneo & Biolzi, 2010) carbon, polypropylene, steel Polypropylene fibers with other hybrid fibers create a negative effect on the performance of concrete under elevated temperature. (Dawood, Mohammad, Abbas, & Mannan, 2018)…”
Section: Author Refmentioning
confidence: 99%
“…The f' c(600d) reached 110.7 MPa for the 400C-180WP mixture, while this was only 79.5 MPa for the 400C-180LF mixture (Table 3), given the dilution effect that resulted from the presence of inert LF materials [12,13]. Regardless of testing age, it is important to note that the f' c values were always higher for mixtures containing combinations of WP together with MK and SF, as compared to SCC prepared with only WP (Table 3).…”
Section: Compressive Strength and Its Evolution Over Timementioning
confidence: 99%
“…Tested mixtures contained up to 120 kg/m 3 LF, 250-400 kg/m 3 CEM, and water-to-powder ratio (w/p) varying from 0.38 to 0.72. The LF is not reactive with calcium hydroxide; however, many studies proved its efficiency to promote nucleation and C-S-H precipitation during cement hydration [12,13,14]. Silva and Brito [6] reported that the substitution of CEM by large FA and/or LF volumes (i.e., up to 65%) can substantially alter the SCC pore structure and durability.…”
Section: Introductionmentioning
confidence: 99%